Peran Budaya Organisasi Sekolah dan Kepuasan Guru dalam Meningkatkan Prestasi Siswa - Anisah Anisah; Eka Wahyu Hidayat (Syntax Idea)
Cultural organizations in the context of educational management, recently there have been many interesting researchers. They study cultural organizations with the background of educational institutions both at the secondary and tertiary levels. The aim of this research is to examine the role of school organizational culture and teacher satisfaction in improving student achievement. The research method used in this research is library research. The data used in this study were secondary data in the form of books, scientific journals and various relevant references collected through library research. The results showed that teachers have a central role in student learning. With rapidly expanding classrooms, resource constraints, and increasing tensions for personal responsibility for student learning outcomes, teachers face challenges on multiple fronts. Reform efforts have largely focused on increasing teacher effectiveness and student achievement, neglecting the organizational role of schools and teacher job satisfaction, which are critical to student success.